READING CULTURE AS A TYPE OF SOCIETY'S CULTURE - Abdullaeva Ikbola Mokhirovna (Sciental Journals Publishing, 2025)
The article considers reading culture as a type of culture of society. Reading culture influences social structures and interactions in society. Joint reading and discussion of literature contribute to the formation of communities united by common interests and values. Reading contributes to the socialization of the individual by familiarizing him or her with the cultural norms and values of society. Literature of various genres reflects social realities and helps readers better understand social processes and human interaction.
Keywords: Reading, reading culture, fiction, images of heroes, moral values, social development, humanistic values, cultural heritage, individual consciousness